Uma ferramenta de autoria para o desenvolvimento de jogos móveis baseados em localização com realidade aumentada - Nolêto, Carleandro de Oliveira (2015)
Location-based mobile games are a special type of game where location technologies are employed to track players and to alter the rules of the games. Such games are a subclass of pervasive games whose playability advances according to the location of players. This work proposes an authoring tool to develop location-based mobile games enhances with augmented reality features. This tool was conceived from research studies on authoring tools and pervasive games. By analysing the related works, we have compiled the most common features of location-based mobile games and the main aspects presented in authoring tools for developing these games. Moreover, we have used focus groups to both enhance the creation of new scenarios for location-based mobile games and improve the usage of augmented reality in such games. Ultimately, we have compiled a set of requirements to design a software architecture for the development of an authoring tool. The designed architecture is composed of a server to manage running games, a web based system for developing these games, and a mobile application in which the games are executed. The main goal of this work is to provide a software solution that allows non-programmers to design, build and execute location-based mobile games. To assess the proposed work, we have designed and implemented a game called "Battle for Fortaleza" using the authoring tool. Besides, we have conducted interviews with users to validate the utility and the easiness of the tool to develop location-based mobile games.